Wybrane uwarunkowania rynku dobrowolnych ubezpieczeń zdrowotnych w krajach europejskich - Borda, Marta (Selected Conditions of the Voluntary Health Insurance Market in the European Countries, 2008)
The paper deals with problems concerning voluntary (private) health insurance offered in the European countries, which in practice supplements, improves or relatively seldom substitutes the public health care services. The stress is put on the main factors creating the possibilities for development of voluntary health insurance products, such as the volume and structure of health care expenditure, the range of services guaranteed in the basic part of health care system, and selected demographic and social conditions. The European countries' experiences in functioning voluntary health insurance can be useful for Poland where there is a need for more intensive, than so far, development of health insurance market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 30-38